US interest allocation rules effects and policy - Altshuler, Rosanne; Mintz, Jack M. (1994)
One of the important changes of the 1986 tax reform for U.S. multinationals is related to the allocation of interest expense. Prior to 1986, U.S. companies allocated domestic interest expense to the income of foreign affiliates on a non-consolidated basis according to the distribution of gross income or assets. After 1986, a U.S. multinational is required to allocate domestic interest expense on a consolidated basis according to the distribution of U.S. and foreign assets. We analyze the impact of the new interest allocation rules on the financial and investment decisions of U.S. multinationals using data from a survey of multinationals assembled by Price Waterhouse. We find that the allocation of interest expense increases the marginal cost of U.S. debt by about 38 percent for firms with excess foreign tax credits. Our empirical tests suggest that firms have altered the location of their borrowings in response to the new rules. We also find that the requirement to allocate interest expense has a significant impact on the effective tax rate faced by U.S. multinationals. For U.S. domestic investments, the interest allocation rules increase the U.S. effective rate from 17.6 percent to 21.9 percent. The rules also increase the effective tax rates on foreign investments made by U.S. firms.
Keywords: Multinationales Unternehmen; Steuer; Ökonometrisches Modell; International business enterprises -- Taxation -- United States -- Econometric models; Investments, American -- Taxation -- Econometric models; USA